Anterior and posterior tibial anesthetic block in diabetic foot surgery. - José Julio Ojeda González; Evangelina Dávila Cabo; Remberto González Enoa; Obdulio Rodríguez García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
Fundament: Diabetes Mellitus is a disease of high and increasing prevalence and its complications follow a parallel course. Its morbidity is derived from its own complications which are produced at a long or short term and peripheral vascular disease hihglights among them.Objective: to check the usefulness of the anterior and posterior blockade of the tibia for the surgery of the diabetic foot. Method: Prospective study carried out from January to December 2003 at the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ to patients who are carriers of a diabetic foot and who were initially assisted at the service of Angiology and later at the service of Anesthesiology when the surgical procedures were decided. All the patients were applied an anterior and posterior blockade of the tibial nerve . The variables measured were: age, weight, height, surgical time, type of surgery, cardiac frequency medium arterial pressure, and classification of patients according to the American Association of Anesthesiology All the patients were applied a scale for assessing pain in three different moments.Result: There was a predominance of females . The blockade of the posterior tibial nerve with lidocaine 1 % in different points permitted the performance of the surgical techniques proposed. The anesthetic procedure was favorable, and economic since the patients did not requiere of the use of analgesic in the post operatory stage.